What Drives Stock Market Development in the Middle East and Central Asia-Institutions, Remittances, or Natural Resources? - Billmeier, Andreas (IMF Working Papers; Working Paper ;, 2007)
In this paper, we assess the macroeconomic determinants of stock market capitalization in a panel of 17 countries in the Middle East and Central Asia, including both hydrocarbon-rich countries and economies without sizeable natural resource wealth. In addition to traditional variables, we include an institutional variable and remittances among the regressors. We find that (i) both institutions and remittances have a positive and significant impact on market capitalization; and (ii) both regressors matter, especially in countries without significant hydrocarbon sectors; whereas (iii) in resource-rich countries, stock market capitalization is mainly driven by the oil price.